BEBAN PEMBUKTIAN PASAL 12 B UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Aurelius, Angeline Theresia; Wijayanto, Bagas Febri; Haryanto, Muh (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This study aims to analyze the reverse burden of proof system applied in Decision No. 34/Pid.Sus-TPK/2022/PN Amb. The research method employs a normative juridical approach, which involves examining case studies related to applicable laws and regulations. The legal materials utilized in this normative legal research include primary and secondary legal sources. The findings reveal that the burden of proof applied in Decision No. 34/Pid.Sus-TPK/2022/PN Amb, concerning the crime of gratification committed by the defendant, former Mayor of Ambon Richard Louhenapessy, is a limited or balanced reverse burden of proof. This system is implemented by both parties, namely the Public Prosecutor and the Defendant. The process begins with the Public Prosecutor establishing the allegations regarding the criminal act of gratification committed by the Defendant. Subsequently, the Defendant, together with their Legal Advisor, demonstrates that the funds received did not originate from the proceeds of the criminal act of gratification. In practice, this limited or balanced reverse burden of proof aligns with the proof process stipulated in the Criminal Procedure Code (KUHAP).